Since you can directly sum two fractions with the same denominator, we can rearrange the sum as follows:
![-(7)/(16) - (5)/(16) - (1)/(4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/asf4wve6ik7z8xccg2232ep6z1kxkzev26.png)
Now we can sum the first two fraction easily:
![(-7-5)/(16) - (1)/(4) = (-12)/(16) - (1)/(4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/blnv1kcm06hq1fon6j10tktoxonm25tj77.png)
We can simplify the first fraction: 12/16=3/4. So, we can sum the two fractions again because they have the same denominator:
![(-12)/(16) - (1)/(4) = (-3)/(4) - (1)/(4) = (-3-1)/(4) = (-4)/(4) = -1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/worn7buuf6ur97o3adfaas12i50gergnh1.png)